The Mediation Effect of Individual Value Conformity With the Organization in the Influence of Corporate Image and Organizational Culture on Employee Engagement of Gen Z in Jakarta - Siti Munajah; Wilfridus B. Elu; Rini Yayuk Priyati (PT FORMOSA CENDEKIA GLOBAL, 2024)
As the number of Gen Z entering companies continues to increase every year, companies must understand the characteristics of Gen Z, especially how they participate in their careers in the company. The purpose of this study is to see how the mediation of Person Organization Fit impacts the influence of Employer Branding and Organizational Culture on Employee Engagement of Gen Z in Jakarta. For this study, this quantitative model was used to distribute questionnaires to Gen Z members who have lived and worked in Jakarta for at least one year. The online distributed questionnaire consisting of 84 statements was completed by 110 valid participants. SmartPLS was used to analyse the data through hypothesis testing and measurements were made using a Likert scale (5 points). The results showed that: (1) Employer Branding affects the Person Organization Fit of gen Z in Jakarta, (2) Employer Branding affects Employee Engagement of gen Z in Jakarta, (3) Organizational Culture affects the Person Organization Fit of gen Z in Jakarta, (4) Organizational Culture does not affect Employee Engagement of gen Z in Jakarta, (5) Person Organization Fit affects Employee Engagement in gen Z in Jakarta, (6) Person Organization Fit cannot mediate Employer Branding affects Employee Engagement in gen Z in Jakarta, (7) Person Organization Fit can mediate Organizational Culture affects Employee Engagement in gen Z in Jakarta.